Servicio Geológico; Nacional de Nicaragua - Camacho Tirado, Jime | Levy Rodríguez, Enrique | Bengoechea G. dolfo, - | Martínez Navas, Pablo | Solórzano Marin, Roberto (Ministerio de Economía, 1962)
Bengoechéa G. Adolfo J.